If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7e + -5 = 10e + 13 Reorder the terms: -5 + 7e = 10e + 13 Reorder the terms: -5 + 7e = 13 + 10e Solving -5 + 7e = 13 + 10e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-10e' to each side of the equation. -5 + 7e + -10e = 13 + 10e + -10e Combine like terms: 7e + -10e = -3e -5 + -3e = 13 + 10e + -10e Combine like terms: 10e + -10e = 0 -5 + -3e = 13 + 0 -5 + -3e = 13 Add '5' to each side of the equation. -5 + 5 + -3e = 13 + 5 Combine like terms: -5 + 5 = 0 0 + -3e = 13 + 5 -3e = 13 + 5 Combine like terms: 13 + 5 = 18 -3e = 18 Divide each side by '-3'. e = -6 Simplifying e = -6
| 2x+5=6x+45 | | 14d-93=4957d | | -11c+32=104-5c | | -5b-19=5-13b | | (x+5)(x-7)=13 | | x+x+(x+5)+(x+5)=58 | | 9x-78=4x-8 | | 2(x-6)=28-6x | | 93-3x=42x+18 | | P=12x-5y | | 3p+5=7p-3 | | 4x-2=115-9x | | 4x-2=4x+32 | | 9x+2=4x+32 | | 6(n+4)=78 | | 2x^2+26x+84=0 | | 9x^2+19x+2=0 | | 10n+3=2 | | 6x+7=13+1x | | 5n=-6 | | 90-5x=31x+22 | | 9-8x=89-43x | | -13x-4=7-8x | | 12-9x=84-23x | | 4x+14=-22-8x | | 8x+8=5x-17 | | 6x-8(4x+7)+10=3 | | 8x+4=4x+2 | | 54x^3=2x | | 12x^6+3=2x^6+1 | | 2+1x=3x | | 3-(x+1)=4x-6 |